A new procedure for the lithic fraction characterization in marine sediments from high productivity areas: Optimization of analytical and statistical procedures. (12th March 2015) - Povea, Patricia; Cacho, Isabel; Moreno, Ana; Menéndez, Melisa; Méndez, Fernando J.
Abstract: The lithogenic fraction in marine sediments can be a key proxy to reconstruct past changes in atmospheric circulation, river runoff among other sedimentary processes. But, accurate isolation of the lithic component within biogenic‐rich sediments can be particularly challenging in areas of high marine productivity. We present an experiment to isolate and characterize this lithogenic fraction that ensures the full elimination of biogenic and authigenic components. This experiment demonstrates that standard procedures used in most of the studies of terrigenous fraction in marine sediments, are inadequate to remove efficiently most of the biogenic components in sediments from high productivity regions such as the Eastern Equatorial Pacific. The experiment reviews each of the procedure steps designed for the removal of organic matter, carbonate, Fe‐Mn oxides, and biogenic silica. The most critical steps were the removal of organic matter incorporated in fecal pellets, and the elimination of the biogenic silica. The continuous monitoring of the grain‐size distribution of the samples along the experiment steps allows evaluating the impact that an inadequate procedure can induce on the grain size. Finally, lithic grain‐size distributions were characterized using k‐means statistical technique providing objective information for climate interpretation. The proposed approach ensures the quality of the results and allows magnifying the information provided by the lithic fraction in marine sediments.